Co-transplantation of mesenchymal stem cells makes haploidentical HSCT a potential comparable therapy with matched sibling donor HSCT for patients with severe aplastic anemia. (October 2020) - Liu, Zenghui; Wu, Xiaoxiong; Wang, Shunqing; Xia, Linghui; Xiao, Haowen; Li, Yonghua; Li, Hongbo; Zhang, Yuping; Xu, Duorong; Nie, Danian; Lai, Yongrong; Wu, Bingyi; et al.
The application of haploidentical hematopoietic stem cell transplantation (HSCT) with mesenchymal stem cell (MSC) infusion as a treatment regimen for severe aplastic anemia (SAA) has been reported to be efficacious in single-arm trials. However, it is difficult to assess without comparing the results with those from a first-line, matched-sibling HSCT. Herein, we retrospectively reviewed 91 patients with acquired SAA. They received HSCT from haploidentical donors combined with MSC transfer (HID group). We compared these patients with 103 others who received first-line matched-sibling HSCT (MSD group) to evaluate relative treatment efficacy. Compared with the patients in the MSD group, those in the HID group presented with higher incidences of grades II–IV and III–IV acute graft versus host disease (aGvHD) and chronic graft versus host disease (cGvHD) ( p  < 0.05). However, the incidence of myeloid and platelet engraftment, graft failure, poor graft function, and extensive cGvHD were comparable for both groups. The median follow-up was 36.6 months and the 3-year overall survival rate was similar for both groups (83.5% versus 79.1%). Univariate and multivariate analyses revealed that time intervals greater than 4 months from diagnosis to transplantation, experienced graft failure, poor graft function, or grade III–IV aGvHD were significantly associated with adverse outcomes. All HID patients received MSC co-transplantation with hematopoietic stem cells. However, the infused MSCs were derived from umbilical cord (UC-MSC group; 43 patients) or bone marrow (BM-MSC group; 48 patients) and were administered at different medical centers. We first compared the outcomes between the two groups and detected that the BM-MSC group exhibited lower incidences of grade III–IV aGvHD and cGvHD ( p  < 0.05). This study suggests that co-transplantation of hematopoietic and MSCs significantly reduces the risk and incidence of graft rejection and may effectively improve overall survival in patients with SAA even in the absence of closely related histocompatible donor material.